2002
DOI: 10.1034/j.1600-0501.2002.130504.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone response to alteration of surface topography and surface composition of sandblasted and acid etched (SLA) implants

Abstract: The titanium surface obtained by sandblasting and etching (SLA) is an easily alterable surface that smears and loose its typical texture. In addition, the etching process modifies the surface composition of commercially pure titanium; the latter contains titanium and an added 20-40% of titanium hydride. Therefore, the influence of a heavy surface alteration and the influence of the composition at the SLA surface, i.e. with and without titanium hydride, were investigated in vivo. Three implant groups were inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 10 publications
1
55
0
Order By: Relevance
“…Perrin et al 12) also reported that the presence of a high and unusual amount hydrogen in etched titanium did not play a significant role in bone response. Therefore, differences in cell proliferation cannot be explained by surface properties such as roughness and composition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Perrin et al 12) also reported that the presence of a high and unusual amount hydrogen in etched titanium did not play a significant role in bone response. Therefore, differences in cell proliferation cannot be explained by surface properties such as roughness and composition.…”
Section: Discussionmentioning
confidence: 98%
“…This is due to the high surface roughness of SLA produced by grit blasting and acid etching, with the latter resulting in an increase in sub-surface hydrogen concentration and the formation of titanium hydride 10) . Surface topology is an important factor for biological interactions at the interface between implants and living tissue 11,12) . In the same vein, surface wettability is another important factor that influences the interactions between the implant surface and the surrounding environment 13,14) .…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) demonstrated that these shiny spots correspond to smearing of the soft surface with alteration of the microtopography. 9 This trait is not specific to the SLA surface but rather is common to all etched surfaces. The etching process carves the titanium surface at a depth of 2 to 5 mm and leaves a soft and smearable surface.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, the efforts are being steered towards separating the effects of surface chemistry and topography [13,14] on the response of osteoblasts, in which the roughness is varied but the chemical composition is maintained constant. In other studies [15,16], acid treatments have been applied after the blasting process and thus obtaining a micro roughness on the surface and a reduction of the number of particles remaining on the surface. Nevertheless, it is not clear that the presence of the particles remaining after the blasting process on the surface can produce a deleterious effect on the in vivo implantation.…”
Section: Introductionmentioning
confidence: 99%